The Effect of Service Quality in International Airport I Gusti Ngurah Rai on Satisfaction, Image, and Tourists Loyalty Who Visited Bali - Manulang, Saroha; Bendesa, I Komang Gde; Darma Putra, I Nyoman (E-Journal of Tourism; Volume 2 Number 1 (March 2015), 2015)
Airport are the first and the last contact point for tourists when they arrive at their holiday destination. Therefore, the airport facilities are a source of first impression that effect the quality expectations of the tourists on holiday activities. Bali as a world class tourism destination to develop and renovate the Ngurah Rai International Airport in order to improve quality of service in order to give higher satisfaction for tourists visiting Bali. Based on this study aims to determine (1) the effect of quality of service to tourists' satisfaction and the image of Bali tourism; (2) the effect of the image of tourism and the quality of service to the loyalty of tourists visiting Bali; (3) the effect of the satisfaction of tourists to the tourism image and loyalty of tourists visiting Bali; (4) the effect of indirect tourism image of the traveler loyalty through satisfaction of tourists; (5) service quality indirectly traveler loyalty through tourism image; and (6) to determine the rating opinion on the quality of service Bali's Ngurah Rai International Airport. Population of this research was all foreign tourists visiting Bali through Ngurah Rai Airport at the time of the research. The research samples included 348 respondents were chosen with nonprobability sampling. accidental sampling technique. Data collected through questionnaires, interviews and observations. The collected data were analyzed with SERVQUAL, Importance Performance Analysis (IPA), and Structural Equation Modelling (SEM) for hypothesis testing. The results showed (1) the quality of service Bali's Ngurah Rai International Airport is a positive effect on tourist satisfaction and the image of Bali tourism; (2) the image of tourism and service quality Bali's Ngurah Rai International Airport is a positive effect on loyalty rating; (3) The traveler satisfaction positive effect on tourism image and loyalty of tourists visiting Bali; (4) Tourism image positive effect on loyalty through satisfaction of tourists; (5) service quality Bali's Ngurah Rai International Airport affect the tourist loyalty through tourism image; and (6) overall rating opinion on the quality of service in the high category, with the highest quality opinions contained in the tangible dimension and the opinion of the lowest quality is below average are in the dimension of reliability.
Keywords: Service Quality, Satisfaction, Tourism Image, Loyalty, I Gusti Ngurah Rai International Airport